Composition for light anti-reflection adhesive film, light anti-reflection adhesive film as well as preparation method and application of light anti-reflection adhesive film

By using a light-enhancing adhesive film crosslinked with grafted fluorescent carbon nanodots and POE grafted particles in perovskite batteries, the damage problem of perovskite batteries under ultraviolet irradiation is solved, and the photoelectric conversion efficiency and stability are improved , extends battery life.

CN119264840APending Publication Date: 2025-01-07SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411599032.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Perovskite batteries are damaged under ultraviolet irradiation, which affects their photoelectric conversion efficiency and service life. The existing adhesive film has limited effect on ultraviolet irradiation, and the stress effect of high temperature irradiation affects the stability of the battery.

Method used

Using a composition containing grafted fluorescent carbon nanodots, POE grafted particles, surfactants, silane coupling agents, antioxidants and photoinitiators, a light-reflective adhesive film is formed through cross-linking reaction, fluorescent carbon nanodots and polymers. Monomer connection improves dispersion and crosslinking, and enhances the photoconversion performance and stability of the adhesive film.

Benefits of technology

Effectively convert ultraviolet light into visible light, reduce damage to perovskite batteries, improve photoelectric conversion efficiency and environmental stability, extend battery life, and enhance the film's ultraviolet bleaching resistance and mechanical stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264840A_ABST
    Figure CN119264840A_ABST
Patent Text Reader

Abstract

The invention provides a composition for a light anti-reflection adhesive film, the light anti-reflection adhesive film, and a preparation method and application of the light anti-reflection adhesive film. The composition is prepared from the following components in parts by mass: 50 to 80 parts of grafted fluorescent carbon nanodots, 20 to 50 parts of POE (Polyolefin Elastomer) grafted particles, 0.5 to 10 parts of a surfactant, 2 to 3 parts of a silane coupling agent, 0.5 to 1 part of an antioxidant, 0.5 to 1 part of a curing agent and 0.5 to 1 part of a photoinitiator, the grafted fluorescent carbon nanodots comprise fluorescent carbon nanodots and polymer monomers grafted on the fluorescent carbon nanodots, the POE grafted particles comprise POE particles and silane substances grafted on the POE particles, and the polymer monomers and the silane substances can be combined through a cross-linking reaction; the grafted fluorescent carbon nanodots are used for converting incident light into emergent light, and the wavelength of the emergent light is larger than that of the incident light. The grafted fluorescent carbon nanodots and the POE grafted particles are crosslinked to form an optical path in the light anti-reflection adhesive film, so that the conversion rate of the light anti-reflection adhesive film for converting ultraviolet light into visible light is improved, and the damage of the ultraviolet light to a battery is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of perovskite cells, and specifically relates to a composition for a light-reflecting adhesive film, a light-reflecting adhesive film, and a preparation method and application thereof. Background Art

[0002] Solar energy is a clean, renewable energy source with broad application prospects. Among them, solar cells are key devices that directly convert solar energy into electrical energy. Perovskite cells are a new type of solar cell that has attracted widespread attention in recent years due to its high efficiency and low cost.

[0003] During use, perovskite cells are exposed to ultraviolet rays in sunlight, which not only affects the photoelectric conversion efficiency of perovskite cells, but also may damage their internal structure and affect the service life of the battery. Therefore, how to effectively prevent ultraviolet rays from damaging perovskite cells and improve the environmental stability of perovskite cells is an important issue facing current perovskite cell technology.

[0004] The existing technology uses some organic or inorganic UV absorbing materials to modify ordinary packaging materials such as POE film, but this has limited improvement on the UV absorption effect of the packaging material and cannot completely protect the perovskite battery from UV damage. In addition, due to the sensitive nature of the perovskite material, high temperature irradiation will cause stress on the perovskite battery due to the thermal expansion of the existing film, thereby affecting the stability and life of the battery, which will affect the efficiency and stability of the perovskite battery. Summary of the invention

[0005] In order to solve all or part of the above technical problems, the present invention provides the following technical solutions:

[0006] One of the purposes of the present invention is to provide a composition for an optical anti-reflection adhesive film, which comprises, by weight: 50 to 80 parts of grafted fluorescent carbon nanodots, 20 to 50 parts of POE grafted particles, 0.5 to 10 parts of a surfactant, 2 to 3 parts of a silane coupling agent, 0.5 to 1 part of an antioxidant, 0.5 to 1 part of a curing agent and 0.5 to 1 part of a photoinitiator;

[0007] Wherein, the grafted fluorescent carbon nanodots include fluorescent carbon nanodots and polymer monomers grafted on the fluorescent carbon nanodots, the POE grafted particles include POE particles (polyethylene octene co-elastomer) and silane substances grafted on the POE particles, and the polymer monomers and the silane substances can be combined through a cross-linking reaction;

[0008] Furthermore, the grafted fluorescent carbon nanodots are used to convert incident light into outgoing light, and the wavelength of the outgoing light is greater than the wavelength of the incident light.

[0009] The present invention finds that if the fluorescent carbon nanodots are directly added to the composition, the dispersibility of the fluorescent carbon nanodots is poor, resulting in the inability to evenly disperse the fluorescent carbon nanodots in the adhesive film; and the carbon dots have weak adhesion to the surface of the adhesive film, thereby reducing the light conversion performance of the adhesive film. The present invention grafts the fluorescent carbon nanodots onto the polymer monomer, and the polymer monomer can be connected to the POE grafted particles in the composition through chemical bonds, thereby improving the dispersibility of the fluorescent carbon nanodots, and increasing the crosslinking of the grafted fluorescent carbon nanodots with the silane coupling agent, while improving the compatibility of the adhesive film with the grafted fluorescent carbon nanodots, and enhancing the strength of the adhesive film after curing; in addition, the addition of a surfactant to the composition can reduce the surface tension of the adhesive film precursor liquid, thereby increasing the adhesion to the glass interface.

[0010] In some embodiments, the grafted fluorescent carbon nanodots include grafted fluorescent carbon nanodots of a first particle size and grafted fluorescent carbon nanodots of a second particle size, the particle size range of the grafted fluorescent carbon nanodots of the first particle size is 20 to 50 nm, the particle size range of the grafted fluorescent carbon nanodots of the second particle size is 10 to 20 nm, and the mass ratio of the grafted fluorescent carbon nanodots of the first particle size to the grafted fluorescent carbon nanodots of the second particle size is 20 to 30:40 to 60. The present invention can improve the density of carbon nanodots in the film by using grafted fluorescent carbon nanodots of different particle sizes; and the carbon dots of the second particle size are smaller and fill in the gaps of the carbon dots of the first particle size, thereby forming a good optical path, and compared with the existing light conversion film, the light conversion performance is significantly improved.

[0011] In some embodiments, the mass ratio of the fluorescent carbon nanodots to the polymer monomers in the grafted fluorescent carbon nanodots is 50-70:10-20.

[0012] In some embodiments, the grafted fluorescent carbon nanodots can convert ultraviolet light into visible light.

[0013] In some embodiments, the fluorescent carbon nanodots are nitrogen-doped fluorescent carbon nanodots. By introducing the N element, the core structure of the carbon nanodots can be regulated, thereby improving their chemiluminescent properties; this regulation not only improves the chemiluminescent brightness and efficiency of the carbon nanodots, but also makes their performance have obvious advantages over traditional organic dyes. Preferably, the nitrogen doping amount is 5 to 15 wt%.

[0014] In some embodiments, the raw materials of the fluorescent carbon nanodots include aniline compounds and / or amino acid compounds.

[0015] In some embodiments, the aniline compound includes one or more combinations of aniline, p-phenylenediamine, diphenylamine, m-phenylenediamine, p-nitroaniline, m-phenylenediamine, o-toluidine, N-methylaniline, p-toluidine, 3,4-dimethylaniline, 2,6-dichloroaniline, 2,6-dimethylaniline or 1,2-phenylenediamine, but is not limited thereto.

[0016] In some embodiments, the amino acid compound includes one or a combination of more of phenylalanine, tyrosine, histidine, proline or pyrrolysine, but is not limited thereto.

[0017] In some embodiments, the method for preparing the grafted fluorescent carbon nanodots includes:

[0018] converting the raw material into fluorescent carbon nanodots;

[0019] sequentially acidifying, acylating and alcoholizing the fluorescent carbon nanodots;

[0020] Then, a mixed reaction system containing the fluorescent carbon nanodots, the polymer monomer and the oxidant is subjected to a grafting reaction to obtain the grafted fluorescent carbon nanodots.

[0021] In the presence of the oxidant, the free radicals on the fluorescent carbon nanodots undergo a shrinkage grafting reaction with the polymer monomer.

[0022] The method for converting the raw material into fluorescent carbon nanodots can adopt any existing preparation method, and the present invention is not particularly limited to this. Exemplarily, the method for preparing fluorescent carbon nanodots includes: providing a solution containing the raw material, heating the solution to 150-250° C. by a pulsed laser heating method, and maintaining it for 3-6 hours, so that the carbon source reacts to form fluorescent carbon nanodots.

[0023] In some embodiments, acidification, acylation and alcoholization of the fluorescent carbon nanodots in sequence specifically include:

[0024] The fluorescent carbon nanodots and the oxidizing acid are mixed in a mass ratio of 5 to 30:50 to 80, and ultrasonically treated for 1 to 3 hours, and then the temperature is adjusted to 55 to 135° C., and the mixture is reacted under stirring and reflux for 0.1 to 48 hours, and then separated and dried to obtain acidified fluorescent carbon nanodots;

[0025] The acidified fluorescent carbon nanodots and thionyl chloride are mixed in a mass ratio of 10-20:70-90, and ultrasonically treated for 1-3 hours, and then the temperature is adjusted to 55-135° C., and reacted for 2-5 hours under light-proof, stirring, and reflux conditions, and separated and dried to obtain acylated carbon nanodots;

[0026] The acylated carbon nanodots and ethylene glycol are mixed in a mass ratio of 20-40:60-90, subjected to ultrasonic treatment for 1-3 hours, separated, and dried to obtain alcoholized carbon nanodots.

[0027] In some embodiments, the grafting reaction specifically includes: mixing the alcoholized carbon nanodots, an oxidant, a polymer monomer and a solvent to obtain a mixed reaction system, wherein the mass ratio of the alcoholized carbon nanodots, the oxidant and the polymer monomer in the mixed reaction system is 60-80:1-5:10-20; reacting the mixed reaction system at a temperature of 80-130°C for 3-10 hours, and obtaining grafted fluorescent carbon nanodots after separation and drying. The fluorescent carbon nanodots in the grafted fluorescent carbon nanodots are connected to the polymer monomer via a CH bond or a CO bond.

[0028] In some embodiments, the preparation method of the grafted fluorescent carbon nanodots also includes: ball milling the dried grafted fluorescent carbon nanodots for 0.5 to 2.5 hours to obtain first particle size grafted fluorescent carbon nanodots with a particle size of 20 to 50 nm; ball milling the dried grafted fluorescent carbon nanodots for 3 to 5 hours to obtain second particle size grafted fluorescent carbon nanodots with a particle size of 10 to 20 nm.

[0029] In some embodiments, the oxidant used in the grafting reaction includes one or more of peracetic acid, sulfuric acid, chromic acid, and nitric acid.

[0030] In some embodiments, the polymer monomer includes an olefin polymer monomer.

[0031] In some preferred embodiments, the olefin polymer monomer includes one or a combination of polystyrene, diisobutylene, 1,3-butadiene or 2-methylpropylene.

[0032] In some embodiments, the silane material grafted onto the POE grafted particles includes methoxysilane.

[0033] In some preferred embodiments, the methoxysilane includes one or a combination of methyldimethoxysilane, vinyltri(2-methoxyethoxy)silane, γ-glycidyloxypropyltrimethoxysilane, and 3-(methacryloyloxy)propyltrimethoxysilane.

[0034] In some embodiments, the POE grafted particles include one or more of POE-methyldimethoxysilane, POE-vinyltri(2-methoxyethoxy)silane, POE-γ-glycidyloxypropyltrimethoxysilane, and POE-3-(methacryloyloxy)propyltrimethoxysilane.

[0035] The present invention finds that the adhesive film formed by the cross-linking reaction of olefin polymer monomers and methoxysilane has not only excellent wavelength conversion function, but also can improve the visible light transmittance and has good resistance to ultraviolet bleaching.

[0036] In some embodiments, the silane substance in the POE grafted particles accounts for 35-45 wt % of the total mass of the POE grafted particles.

[0037] In some embodiments, the surfactant includes one or more of glyceryl monostearate, sucrose fatty acid ester, sorbitan fatty acid ester, propylene glycol fatty acid ester, sodium carboxymethyl cellulose, propylene glycol alginate, cellulose glycolic acid, methyl cellulose and sodium polyacrylate, but is not limited thereto. The surfactant can reduce the surface tension of the film precursor solution and increase its adhesion to the transparent substrate such as glass interface.

[0038] In some embodiments, the silane coupling agent includes one or a combination of two or more of methyldimethoxysilane, vinyltri(2-methoxyethoxy)silane, γ-glycidyloxypropyltrimethoxysilane, and 3-(methacryloyloxy)propyltrimethoxysilane.

[0039] In some embodiments, the curing agent includes one or a combination of two or more of tricyclodecane dimethanol diacrylate, 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, 1,4-butanediol diacrylate, tricyclodecane dimethanol dimethacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, dipentaerythritol hexaacrylate, dipentaerythritol hexaacrylate or 1,6-hexamethylene diisocyanate.

[0040] In some embodiments, the photoinitiator includes one or a combination of two or more of benzoin, benzoin dimethyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin butyl ether, α,α-dimethoxy-α-phenylacetophenone, thiopropoxythioxanthone, isopropylthioxanthone, fluorinated diphenyl titanocene or bis(pentafluorophenyl) titanocene.

[0041] In some embodiments, the antioxidant includes one or a combination of two or more of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, di(2,2,6,6-tetramethyl-4-piperidinyl)sebacate, and n-octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

[0042] A second object of the present invention is to provide a method for preparing a light-reflecting adhesive film, comprising:

[0043] The mixed reaction system containing the composition and the solvent is reacted at a temperature of 60 to 90° C., so that the polymer monomers in the grafted fluorescent carbon nanodots and the POE grafted particles undergo a cross-linking reaction to form a film precursor solution;

[0044] The adhesive film precursor liquid is solidified and subjected to a molding process to obtain the light-enhancing adhesive film.

[0045] In some embodiments, the reaction time is 0.5 to 3 hours.

[0046] In some embodiments, the curing method includes UV lamp irradiation, mercury lamp irradiation, etc., but is not limited thereto.

[0047] In some embodiments, the mass ratio of the composition to the solvent is 30-40:40-50.

[0048] In the above preparation method, the composition is first reacted under the temperature conditions, and then cured to form an adhesive film, which can make the fluorescent carbon nanodots evenly distributed in the adhesive film and form abundant optical pathways. The formed optical anti-reflection film can effectively convert ultraviolet light into visible light that can be absorbed by solar cells, so as to reduce the damage of ultraviolet light to solar cells, improve the efficiency of solar cells to absorb light, and enhance the photoelectric conversion efficiency of solar cells. The optical anti-reflection adhesive film has good stability and will not react with perovskite materials; it can well isolate water and oxygen from corroding solar cells, and improve the environmental stability of solar cells.

[0049] Compared with other photovoltaic films prepared by cast extrusion, which have the disadvantage of uneven thickness, this type of film precursor has excellent rheological properties and can be coated with a thickness-adjustable, uniform film layer through slit coating and screen printing, thereby effectively improving the light transmittance of the film and the light absorption efficiency and photoelectric conversion efficiency of solar cells, and significantly improving product stability and service life.

[0050] The third object of the present invention is to provide a light-enhancing adhesive film, which is prepared by the method described in the above technical solution.

[0051] A fourth object of the present invention is to provide a solar cell packaging structure, comprising: a light-transmitting substrate and the light-anti-reflection adhesive film formed on the light-transmitting substrate, wherein when the packaging structure is packaged in a solar cell, the light-anti-reflection adhesive film is located on a side close to the solar cell.

[0052] In some embodiments, the method for preparing the solar cell packaging structure includes:

[0053] The mixed reaction system containing the composition and the solvent is reacted at a temperature of 60 to 90° C., so that the polymer monomers in the grafted fluorescent carbon nanodots and the silane substances on the POE grafted particles undergo a cross-linking reaction to form a film precursor solution;

[0054] The adhesive film precursor liquid is coated on a light-transmitting substrate, and the adhesive film precursor liquid is solidified to obtain the packaging structure.

[0055] In some embodiments, the method of coating the adhesive film precursor liquid on the light-transmitting substrate includes spraying, slit coating, screen printing, etc., but is not limited thereto. These methods can form the adhesive film precursor liquid on the light-transmitting substrate in one piece.

[0056] In some embodiments, the thickness of the anti-reflection adhesive film is 100 μm to 1000 μm.

[0057] A fifth object of the present invention is to provide a photovoltaic module, comprising a first light-transmitting plate, a first adhesive film, a solar cell, a second adhesive film and a second light-transmitting plate stacked in sequence, wherein at least one of the first adhesive film and the second adhesive film comprises the light-enhancing adhesive film.

[0058] In some embodiments, the solar cell is a perovskite cell.

[0059] The double-layer packaging structure of the photovoltaic module can effectively prevent lead leakage from perovskite cells and perovskite modules. The light-reflection-enhancing film layer provided by the present invention will not react with the perovskite material due to stress, has good compatibility with the perovskite cell, can avoid the influence of the light-reflection-enhancing material on the cell performance, and improves the stability and reliability of the product.

[0060] Compared with the prior art, the present invention has at least the following beneficial effects: the present invention provides a composition for preparing a light-enhancing adhesive film, wherein the grafted fluorescent carbon nanodots are formed by grafting the fluorescent carbon nanodots onto a polymer monomer, and the polymer monomer can undergo a cross-linking reaction with the POE grafted particles in the composition, so that the fluorescent carbon nanodots are evenly distributed in the light-enhancing adhesive film and form an optical path in the light-enhancing adhesive film, thereby effectively improving the conversion efficiency of the carbon nanodots in converting ultraviolet light into visible light, reducing the damage of ultraviolet rays to the battery, and increasing the service life of the solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 is a schematic structural diagram of a packaging structure for a perovskite module in Example 1 of the present invention;

[0062] 100-Perovskite module, 200-Anti-reflection film, 300-Glass cover, 400-Butyl adhesive. DETAILED DESCRIPTION

[0063] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention. The specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.

[0064] Unless otherwise specified, the raw materials and reagents used in the specific embodiments of the present invention are all commercially available.

[0065] Example 1

[0066] (1) Preparation of grafted fluorescent carbon nanodots:

[0067] Phenylalanine and aniline were dispersed in ethanol at a molar ratio of 3:1 to obtain a mixed solution, the concentration of which was 5 mg / mL. The solution was placed in a reactor, subjected to pulse laser heating to a temperature of 150°C, and the reaction was maintained for 3 hours. The reaction product was filtered through a filter membrane, and the solid product obtained by filtration was dried in a vacuum oven to obtain fluorescent carbon nanodots.

[0068] The prepared fluorescent carbon nanodots were added to a mixed acid of peracetic acid and sulfuric acid (the mass ratio of peracetic acid to sulfuric acid was 1:1) in a mass ratio of 1:10, ultrasonically treated for 2 hours, heated to 100°C, stirred and refluxed for 6 hours, cooled, repeatedly rinsed, filtered, and dried to obtain acidified fluorescent carbon nanodots; the acidified fluorescent carbon nanodots and thionyl chloride were mixed in a mass ratio of 10:70, ultrasonically treated for 2 hours, heated to 120°C, stirred and refluxed for 3 hours in the dark, and after the reaction, vacuum filtered and repeatedly washed with anhydrous tetrahydrofuran, and dried to obtain acylated carbon nanodots; the acylated carbon The nanodots and ethylene glycol were mixed in a mass ratio of 20:60, ultrasonically treated for 2 hours, vacuum filtered, and repeatedly washed with anhydrous tetrahydrofuran, separated, and dried to obtain alcoholized carbon nanodots; the alcoholized carbon nanodots, hydrogen peroxide, and polymer monomer polystyrene were added to an ethanol solution in a mass ratio of 70:3:15, placed in a reactor, and then ultrasonically treated for 8 hours, vacuum filtered, and the reaction product was rinsed 4 times, placed in a vacuum drying oven for 3 hours, crushed by ball milling, and by controlling the ball milling time, grafted fluorescent carbon nanodots with particle sizes of approximately 35nm and 15nm were obtained.

[0069] (2) This embodiment provides a composition for preparing an optical anti-reflection adhesive film, and the raw materials are weighed according to the following mass parts:

[0070] 60 parts of the grafted fluorescent carbon nanodots prepared above, wherein the mass ratio of 35 nm to 15 nm grafted fluorescent carbon nanodots is 1:2;

[0071] 40 parts of POE-methyldimethoxysilane;

[0072] 0.5 parts of surfactant glyceryl monostearate;

[0073] 2 parts of silane coupling agent methyl dimethoxy silane;

[0074] 1 part of the antioxidant pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate;

[0075] 0.5 parts of curing agent tricyclodecane dimethanol diacrylate;

[0076] 0.5 parts of photoinitiator benzoin.

[0077] (3) Using the above composition to prepare a light-reflecting adhesive film, specifically comprising the following steps:

[0078] Take 0.5 g of the above composition, mix it evenly with 0.5 g of DMSO, raise the temperature of the mixture to 60° C. and react for 2 hours to obtain a film precursor solution;

[0079] The adhesive film precursor liquid is coated on a glass plate in an integrated manner, and after the coating structure is irradiated with a UV lamp, thereby forming a light-enhancing adhesive film with a thickness of 562 μm on the glass plate.

[0080] (4) The perovskite module is encapsulated using the glass plate containing the light-reflecting adhesive film. The encapsulation structure is as follows: Figure 1 As shown, a glass cover plate 300 containing an anti-reflective adhesive film 200 is respectively arranged on two opposite surfaces of the perovskite module 100. The anti-reflective adhesive film 200 is arranged on both sides close to the perovskite module 100 and is bonded on the left and right sides with butyl adhesive 400.

[0081] Embodiment 2-7

[0082] The only difference between Examples 2-7 and Example 1 is that the carbon source of fluorescent carbon nanodots and the polymer / monomer grafted with fluorescent carbon nanodots are prepared according to the changes shown in Table 1, and the components of the composition and the content of each component are changed according to Table 2.

[0083] Example 8

[0084] The only difference between Example 8 and Example 1 is that Example 8 uses 50 nm grafted fluorescent carbon nanodots and 20 nm grafted fluorescent carbon nanodots, and the mass ratio of the 50 nm grafted fluorescent carbon nanodots to the 20 nm grafted fluorescent carbon nanodots is 1:2.

[0085] Example 9

[0086] The only difference between Example 9 and Example 1 is that Example 8 uses 20 nm grafted fluorescent carbon nanodots and 10 nm grafted fluorescent carbon nanodots, and the mass ratio of the 20 nm grafted fluorescent carbon nanodots to the 10 nm grafted fluorescent carbon nanodots is 1:2.

[0087] Comparative Example 1

[0088] The only difference between Comparative Example 1 and Example 1 is that the fluorescent carbon nanodots are not grafted in Comparative Example 1, and the preparation of the fluorescent carbon nanodots is specifically as follows: phenylalanine and aniline are dispersed in ethanol at a molar ratio of 3:1 to obtain a mixed solution, and the concentration of the mixed solution is 5 mg / mL; the solution is placed in a reactor, and pulsed laser heating is performed to the temperature to reach 150°C, and the reaction is maintained for 3 hours; the reaction product is filtered through a filter membrane, and the filtered solid product is dried in a vacuum oven to obtain fluorescent carbon nanodots.

[0089] The fluorescent carbon nanodots prepared in Comparative Example 1 were used to replace the grafted fluorescent carbon nanodots in Example 1, and the rest of the steps were the same as in Example 1.

[0090] Comparative Example 2

[0091] The only difference between Comparative Example 2 and Example 1 is that Comparative Example 2 does not perform grafting treatment on the fluorescent carbon nanodots, and the preparation of the fluorescent carbon nanodots is specifically as follows: phenylalanine and aniline are dispersed in ethanol at a molar ratio of 3:1 to obtain a mixed solution, and the concentration of the mixed solution is 5 mg / mL; the solution is placed in a reactor, and pulsed laser heating is performed to the temperature to reach 150°C, and the reaction is maintained for 3 hours; the reaction product is filtered through a filter membrane, and the filtered solid product is dried in a vacuum oven to obtain fluorescent carbon nanodots.

[0092] The composition consists of:

[0093] 60 parts of the fluorescent carbon nanodots prepared above;

[0094] 20 parts polystyrene;

[0095] 40 parts of POE-methyldimethoxysilane;

[0096] 0.5 parts of surfactant glyceryl monostearate;

[0097] 2 parts of silane coupling agent methyl dimethoxy silane;

[0098] 1 part of the antioxidant pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate;

[0099] 0.5 parts of curing agent tricyclodecane dimethanol diacrylate;

[0100] 0.5 parts of photoinitiator benzoin.

[0101] The rest is implemented in the same manner as in Example 1.

[0102] Comparative Example 3

[0103] The difference between Comparative Example 3 and Example 1 is that the POE-methyldimethoxysilane grafted particles in Example 1 are replaced by pure POE particles without methyldimethoxysilane, and the rest is the same as Example 1.

[0104] Table 1 Raw materials for preparing grafted fluorescent carbon nanodots in Examples 1 to 7

[0105]

[0106] Table 2 Components and contents of the composition used to prepare the optical anti-reflection adhesive film in Examples 1 to 7

[0107]

[0108] Table 3 Related properties of the light-reflecting adhesive films in the embodiments of the present invention and the comparative examples

[0109]

[0110]

[0111] In summary, Examples 1 to 7 are film samples prepared by grafting fluorescent carbon nanodots and POE grafted particles, and their light transmittance is between 91% and 96%, which is significantly higher than the 84% to 85% of the film samples prepared by the fluorescent carbon nanodots or pure POE particles in Comparative Examples 1 to 3 without grafting, and the photoelectric conversion efficiency of the perovskite cells of Examples 1-9 can reach 20.5 to 23.01%, which is significantly higher than the comparative example, indicating that the use of the example samples for battery packaging can ensure that the perovskite cell absorbs enough visible light to improve the photoelectric conversion efficiency of the cell. After the example samples were illuminated for 300 hours, the cell had a small efficiency attenuation, indicating that the film can effectively convert ultraviolet light into visible light absorbed by the perovskite cell, reducing the damage of ultraviolet light to the perovskite cell and improving the environmental stability of the cell.

[0112] In addition, the fluorescent carbon nanodots are grafted so that the polymer monomers on the grafted fluorescent carbon dots can be connected to the grafted POE nanoparticles through chemical bonds, thereby increasing the crosslinking property with silane, and at the same time improving the compatibility of the adhesive film with the grafted fluorescent carbon nanodots, and enhancing the strength of the adhesive film after curing. Since the present invention grafts the fluorescent carbon nanodots, the hydrogen atoms, hydroxyl groups, and carboxyl groups on the polymer monomers grafted on the fluorescent carbon nanodots and the silicon atoms of the silane-type substances grafted on the POE will undergo condensation reactions with the hydroxyl groups to form stable Si-O bonds or Si-C bonds. This reaction can improve the mechanical stability and durability of the material, improve the strain resistance of the adhesive film in a high temperature environment, prevent the adhesive film from being strained and thus causing mechanical effects on the perovskite battery, and improve the life of the perovskite battery.

[0113] In addition, the addition of surfactants can reduce the surface tension of the film precursor liquid, increase the adhesion with the glass interface, and increase the adhesion ability of the film to the substrate. Compared with the comparative sample, the film can more effectively block the corrosion of water and oxygen on the battery, thereby improving the stability of the final perovskite battery.

[0114] The various aspects, embodiments, features and examples of the present invention should be considered to be illustrative in all aspects and are not intended to limit the present invention, and the scope of the present invention is defined only by the claims. Without departing from the spirit and scope of the claimed invention, other embodiments, modifications and uses will be apparent to those skilled in the art. In addition, the inventors of this case have also tested with other raw materials, process operations and process conditions described in this specification with reference to the aforementioned embodiments, and all obtained relatively ideal results. Although the present invention has been described with reference to illustrative embodiments, it will be understood by those skilled in the art that various other changes, omissions and / or additions can be made without departing from the spirit and scope of the present invention, and the elements of the embodiments can be replaced by substantial equivalents. In addition, many modifications can be made without departing from the scope of the present invention to adapt specific situations or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but the terms first, second, etc. are used to distinguish one element from another.

Claims

1. A composition for an optical anti-reflection adhesive film, characterized in that: The composition comprises, by weight: 50 to 80 parts of grafted fluorescent carbon nanodots, 20 to 50 parts of POE grafted particles, 0.5 to 10 parts of a surfactant, 2 to 3 parts of a silane coupling agent, 0.5 to 1 part of an antioxidant, 0.5 to 1 part of a curing agent and 0.5 to 1 part of a photoinitiator; Wherein, the grafted fluorescent carbon nanodots include fluorescent carbon nanodots and polymer monomers grafted on the fluorescent carbon nanodots, the POE grafted particles include POE particles and silane substances grafted on the POE particles, and the polymer monomers and the silane substances can be combined through a cross-linking reaction; Furthermore, the grafted fluorescent carbon nanodots are used to convert incident light into outgoing light, and the wavelength of the outgoing light is greater than the wavelength of the incident light.

2. The composition according to claim 1, characterized in that: The mass ratio of the fluorescent carbon nanodots to the polymer monomer in the grafted fluorescent carbon nanodots is 50-70:10-20; and / or, the grafted fluorescent carbon nanodots are capable of converting ultraviolet light into visible light; And / or, the fluorescent carbon nanodots are nitrogen-doped fluorescent carbon nanodots; And / or, the grafted fluorescent carbon nanodots include grafted fluorescent carbon nanodots with a first particle size and grafted fluorescent carbon nanodots with a second particle size, the particle size range of the grafted fluorescent carbon nanodots with the first particle size is 20 to 50 nm, the particle size range of the grafted fluorescent carbon nanodots with the second particle size is 10 to 20 nm, and the mass ratio of the grafted fluorescent carbon nanodots with the first particle size to the grafted fluorescent carbon nanodots with the second particle size is 20 to 30:40 to 60.

3. The composition according to claim 1, characterized in that: The silane substance in the POE grafted particles accounts for 35-45 wt % of the total mass of the POE grafted particles.

4. The composition according to claim 1, characterized in that: The polymer monomers include olefin polymer monomers; And / or, the silane substance includes methoxysilane.

5. The composition according to claim 4, characterized in that: The olefin polymer monomer includes one or a combination of polystyrene, diisobutylene, 1,3-butadiene, and 2-methylpropylene; And / or, the methoxysilane includes one or a combination of methyldimethoxysilane, vinyltri(2-methoxyethoxy)silane, γ-glycidyloxypropyltrimethoxysilane, and 3-(methacryloyloxy)propyltrimethoxysilane.

6. The composition according to claim 1, characterized in that: The surfactant includes one or more of glyceryl monostearate, sucrose fatty acid esters, sorbitan fatty acid esters, propylene glycol fatty acid esters, sodium carboxymethyl cellulose, propylene glycol alginate, cellulose glycolic acid, methyl cellulose and sodium polyacrylate; And / or, the silane coupling agent includes one or a combination of two or more of methyldimethoxysilane, vinyltri(2-methoxyethoxy)silane, γ-glycidyloxypropyltrimethoxysilane, and 3-(methacryloyloxy)propyltrimethoxysilane; And / or, the curing agent includes one or a combination of two or more of tricyclodecane dimethanol diacrylate, 1,6-hexanediol diacrylate, tripropylene glycol diacrylate, 1,4-butanediol diacrylate, tricyclodecane dimethanol dimethacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, dipentaerythritol hexaacrylate, dipentaerythritol hexaacrylate or 1,6-hexamethylene diisocyanate; And / or, the photoinitiator comprises one or a combination of two or more of benzoin, benzoin dimethyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin butyl ether, α,α-dimethoxy-α-phenylacetophenone, thiopropoxythioxanthone, isopropylthioxanthone, fluorinated diphenyl titanocene or bis(pentafluorophenyl) titanocene; And / or, the antioxidant includes one or a combination of two or more of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, di(2,2,6,6-tetramethyl-4-piperidinyl)sebacate, and n-octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

7. A method for preparing a light-reflecting adhesive film, characterized in that: include: The mixed reaction system containing the composition of claim 1 to claim 6 and a solvent is reacted at a temperature of 60 to 90° C., so that the polymer monomer in the grafted fluorescent carbon nanodots and the silane substance on the POE grafted particles undergo a cross-linking reaction to form a film precursor solution; The adhesive film precursor liquid is solidified and subjected to a molding process to obtain the light-enhancing adhesive film.

8. A light-anti-reflection film, characterized in that: It is prepared by the method described in claim 7.

9. A solar cell packaging structure, characterized in that: include: A light-transmitting substrate and the light-anti-reflecting adhesive film according to claim 8 formed on the light-transmitting substrate, wherein when the encapsulation structure is encapsulated in a solar cell, the light-anti-reflecting adhesive film is located on a side close to the solar cell.

10. A photovoltaic module, characterized in that: It comprises a first light-transmitting plate, a first adhesive film, a solar cell, a second adhesive film and a second light-transmitting plate which are stacked in sequence, wherein at least one of the first adhesive film and the second adhesive film comprises the light-enhancing adhesive film according to claim 8; Preferably, the solar cell is a perovskite cell.

Citation Information

Cited By

  • Lower conversion film layer and anti-reflection combined film of solar cell, perovskite solar cell and solar cell module

    CN122622478A